Causes of fermentation in canned vegetables - Justin, Edith B. (My University, 1908)
Introduction: When one thinks of the number of people who depend upon canned products for the greater part of their vegetable supply and of the immense amount of labor and capital expended each year in the canning industry, one my readily see the importance of having the vegetables canned in such a manner that the consumer may receive them in perfect condition.
Citation: Justin, Edith B. Causes of fermentation in canned vegetables. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Fermentation; Vegetables; Food; Graduating theses; Senior theses; Theses